2017
DOI: 10.1038/srep44678
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes are coincident with the improvement of clinical symptoms in surgically treated compressed nerve roots

Abstract: Diffusion tensor imaging (DTI) has been widely used to visualize peripheral nerves, but the microstructure of compressed nerve roots can be assessed using DTI. However, there are no data regarding the association among microstructural changes evaluated using DTI, the symptoms assessed using the Oswestry Disability Index (ODI) and the duration of symptoms after surgery in patients with lumbar disc herniation (LDH). Thirty patients with unilateral radiculopathy were investigated using DTI. The changes in the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 28 publications
5
15
1
Order By: Relevance
“…The sensitivity and specificity of FA values for the detection of nerve injury have been reported to be higher than those of ADC values (73.3% and 100% vs. 13.4% and 80%). FA values appear to be superior to ADC values in the diagnosis of lumbosacral radiculopathy, with potential application for post-treatment evaluation 2,1619 . Therefore, in this study, we used FA values for preoperative diagnosis, postoperative evaluation and prognosis of patients with LDH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity and specificity of FA values for the detection of nerve injury have been reported to be higher than those of ADC values (73.3% and 100% vs. 13.4% and 80%). FA values appear to be superior to ADC values in the diagnosis of lumbosacral radiculopathy, with potential application for post-treatment evaluation 2,1619 . Therefore, in this study, we used FA values for preoperative diagnosis, postoperative evaluation and prognosis of patients with LDH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, DTI is widely used in the clinical evaluation of nerve root lesions. Although research has shown a significant negative correlation between the FA value of compressed nerve roots and ODI scores 2 , few studies have evaluated the relationship between the dynamic changes of postoperative DTI indicators and the improvement of clinical symptoms. Therefore, all the patients in this study underwent PTED, and DTI scanning was performed before surgery, as well as 3 days, 1 month, and 3 months post-surgery, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, we observed a promotion of leukemia inhibitory factor (LIF) and VEGF in endometrium and a higher pregnancy rate in embryo implantation dysfunction (EID) mouse model after a hCG co-cultured with PBMCs infusion (25). We also demonstrated administration of hCG co-cultured with PBMCs for 24 hours could significantly improve the adverse pregnancy outcome of RIF patients, especially for women who had undergone four or more implantation failures (26). However, the mechanisms of hCG co-cultured with PBMCs infusion in promoting a receptive endometrium remain unclear.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, the diffusion tensor imaging technique has been used for the structural and functional diagnosis of lumbar nerve damage before and after surgery. [19][20][21][22][23] Regarding surgical procedures, Cho et al [24] demonstrated that their floating technique reduces complications during PELD. In their series of 154 patients, none had ENR injury.…”
Section: Enr Injurymentioning
confidence: 99%